The Influences of Perceived Risk, Ease of Use, Subjective Norm, and Trust Towards Intention of Using E-banking - Hafidz Dhaneswara (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to provide evidence related to the influences of perceived risk, perceived ease of use, subjective norm, and trust towards intention of using e -banking. This research is a quantitative research. The sample used is 273 accounting students of faculty of economics and business Brawijaya University that registered as an active students in academic year of 2015/2016 obtained using nonprobability sampling. This data analysis is conducted using multiple regression analysis and using SPSS program to test the research. Test result shows that perceived risk has negative and significant effect on customer’s intention of using e - banking. Perceived ease of use, subjective norm, and trust have positive and significant effect on customer’s intention of using e-banking. The research shows that perceived risk related into customer’s trust of using e-banking. The variable that most influences on customer’s intention of using e-banking is perceived ease of use variable. The implication of this research as a reference for banking companies in improving the quality and as a marketing strategy to increase customer in using e-banking related to factor of perceived risk, perceived ease of use, subjective norm, and trust.Keywords: perceived risk, perceived ease of use, subjective norm, trust, intention, e-banking